Enhancing BIPA Learners’ Speaking Confidence Through Wordwall in Online Learning - Intan Hamzah; Khairani Putri Salsya; Alvi Raihan Utami; Dyah Aminatun; Mutiara Ayu (English Language Teaching Prima Journal (ELT), 2026)
The integration of digital learning tools in language education has opened new avenues for improving students' communicative competence, particularly in the context of teaching Indonesian to foreign speakers (Bahasa Indonesia bagi Penutur Asing/BIPA). This study investigates the effectiveness of Wordwall, an interactive, game-based online platform, in enhancing the speaking confidence of BIPA learners during online learning. Using a convergent parallel mixed-methods design combining quasi-experimental pretest-posttest measurements with learner questionnaires and structured classroom observation data, data were collected from 30 intermediate-level BIPA students over an eight-week instructional intervention. Quantitative results revealed statistically significant improvements in overall speaking confidence (t(29) = 8.47, p < .001, Cohen's d = 1.54), with the most pronounced gains in willingness to communicate and reduced speaking anxiety. Speaking performance rubric scores also improved significantly across five criteria: fluency, grammatical accuracy, vocabulary range, pronunciation, and interactive competence. Qualitative analysis identified four major themes: affective liberation, lexical empowerment, social belonging and motivation, and self-efficacy growth. These findings suggest that Wordwall, purposefully integrated into online BIPA speaking instruction, serves as a powerful pedagogical tool for dismantling affective barriers to oral communication and building the lexical confidence needed for more fluent and willing participation in Indonesian.